The effects of macroeconomics determinants towards the performance of property stock market in Malaysia / Muhammad Nur Hijazi Jasmon - Jasmon, Muhammad Nur Hijazi (Faculty of Business and Management, 2015)
The aim of this paper is to examine the effects of macroeconomic determinants towards the property stock market performance in Malaysia. The property stock market performance of Malaysia was chosen as the dependent variable in this study. There are five independent variables to be use in the study which are Growth Rate of Gross Domestic Product (GDP), Inflation Rate, Exchange Rate, Money Supply (M2) and Industry Production Output Growth Rate. The data were gathered from annual data year 1985 to 2013. The data was gathered from DataStream and World Data Bank. A multiple linear regression is used in this study. In addition, the econometric tests are employed to observe the relationship of the economic variables to the performance of property stock market in Malaysia. The interactive package E-View is used in order to run the test and analysis on the data collected. Thus, trough the data testing, it is going to show how the variable are related each other. It is expected that the most of the data findings on the variable are going to be significant. This is based on previous study made by many researchers that found the finding are significantly related between dependent and independent variables. As tested by(Thim et al, 2012), (Liow et al, 2006), (Liow, Ibrahim, & Huang, 2014), (Ong, 2013), (West, 2006a), and (Duca, 2007)